Impact of non-fulfillment of the super position principle on the analysis of thermoluminescence glow-curve. (September 2018) - Sadek, A.M.; Kitis, G.
Abstract: The analysis of complex thermoluminescence (TL) glow curves in its individual peaks is achieved by a computerized glow curve deconvolution (CGCD). The correct application of the CGCD requires the fulfillment of the superposition principle (SP), which postulates that the TL peaks have to be independent of each other. In the present work we simulate the application of the CGCD using interactive phenomenological models in which the SP is not fulfilled. The thermoluminescence (TL) processes of four active traps and one thermally disconnected deep trap (TDDT) was simulated over a wide range of doses and under different competition cases. The TL glow-curves were analyzed by the CGCD algorithm and the accuracy of the kinetic parameters and the dose dependence of each trap were investigated over the doses. In most of the simulated cases, the non-fulfillment of the superposition principles has no significant effect on the accuracy of the computed kinetics parameters. Different behaviors of dose response curve were discussed including sub-linear and supra-linear dose dependence. It has been also found that in the case of presence of competitions among the active traps, an almost linear dose response curve can be observed for the last glow-peak in a series of overlapping glow-peaks. Highlights: The impact of non-fulfillment of the SP theorem on the CGCD analysis was discussed. TL glow curves were simulated over a wide range of doses and different conditions. In general, the non-fulfillment of the SP theorem has no effect on the CGCD method.